2014
DOI: 10.1515/ract-2014-2281
|View full text |Cite
|
Sign up to set email alerts
|

Digital liquid-scintillation counting and effective pulse-shape discrimination with artificial neural networks

Abstract: A typical problem in low-level liquid scintillation (LS) counting is the identification of particles in the presence of a high background of and particles. Especially the occurrence of -and -pile-ups may prevent the unambiguous identification of an signal by commonly used analog electronics. In this case, pulseshape discrimination (PSD) and pile-up rejection (PUR) units show an insufficient performance. This problem was also observed in own earlier experiments on the chemical behaviour of transactinide element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, there are few empirical studies on the teaching and learning of English grammar. Foreign language major core journals in China on the knowledge of English grammar teaching and learning found that although some research, respectively, discusses the English grammar knowledge to the predictive power of pragmatic knowledge [8,9] ability to distinguish between training and development trend, English grammar [10], college English teachers and students grammar teaching and learning belief [11], and English grammar knowledge and English and English language skills such as the potential relationship [12], due to adopting the concept of English grammar knowledge or ability and measuring tools, testing the level of task difficulty and subjects of English language levels vary. e result is not the same.…”
Section: Related Workmentioning
confidence: 99%
“…However, there are few empirical studies on the teaching and learning of English grammar. Foreign language major core journals in China on the knowledge of English grammar teaching and learning found that although some research, respectively, discusses the English grammar knowledge to the predictive power of pragmatic knowledge [8,9] ability to distinguish between training and development trend, English grammar [10], college English teachers and students grammar teaching and learning belief [11], and English grammar knowledge and English and English language skills such as the potential relationship [12], due to adopting the concept of English grammar knowledge or ability and measuring tools, testing the level of task difficulty and subjects of English language levels vary. e result is not the same.…”
Section: Related Workmentioning
confidence: 99%